المركز القانوني لكفيل الكفيل (المصدق) في القانون العراقي: دراسة مقارنة - علي, راقية عبد الجبار (Journal of Legal Sciences, 2020)
Ensure authority, contract whereby a person ensure that the implementation of the commitment to the creditor undertakes to fulfill this obligation if he does not do the original debtor and the guarantor of the debt, which he took to ensure his commitment.zValmsedk, the second is the guarantor of the debt after the sponsor, the subject of his commitmentDo not focus on ensuring the religion of the debtor, but the focus is on ensuring the commitment of the sponsor.It is here to be a creditor of three people responsible for one religion they are all of the debtor - the sponsor - authorityThis research deals with the legal status of certified by definition Palmsedk statement and conditions that should be considered in relation to the creditor.And defenses, which has the right to stick it out to pay the creditor's claim his religion.